Short Stature Homeobox-Containing Haploinsufficiency in Seven Siblings with Short Stature - Elizabeth S. Sandberg; Ali S. Calikoglu; Karen J. Loechner; Lydia L. Snyder (Case Reports in Endocrinology)
Deficiency of the short stature homeobox-containing (SHOX) gene is a frequent cause of short stature in children (2–15%). Here, we report 7 siblings with SHOX deficiency due to a point mutation in the SHOX gene. Index case was a 3-year-old male who presented for evaluation of short stature. His past medical history and birth history were unremarkable. Family history was notable for multiple individuals with short stature. Physical exam revealed short stature, with height standard deviation score (SDS) of −2.98, as well as arm span 3 cm less than his height. His laboratory workup was noncontributory for common etiologies of short stature. Due to significant familial short stature and shortened arm span, SHOX gene analysis was performed and revealed patient is heterozygous for a novel SHOX gene mutation at nucleotide position c.582. This mutation is predicted to cause termination of the SHOX protein at codon 194, effectively causing haploinsufficiency. Six out of nine other siblings were later found to also be heterozygous for the same mutation. Growth hormone was initiated in all seven siblings upon diagnosis and they have demonstrated improved height SDS.